Variability of Cetacean Distribution and Habitat Selection in the Alaskan Arctic, Autumn 1982-91 - Moore, Sue E. (ARCTIC, 2000)
Ten years (1982-91) of autumn sighting data from aerial surveys offshore northern Alaska were analyzed to investigate variability in cetacean distribution and habitat selection. Habitat selection indices were calculated for bowhead, white, and gray whales in heavy, moderate, and light ice conditions; and for high, moderate, and low transport (inflow) conditions at Bering Strait. Bowhead whales selected shallow inner-shelf waters during moderate and light ice, and deeper slope habitat in heavy ice conditions (chi², p < 0.05-0.001). White whales selected slope habitat (chi², p < 0.001), and gray whales selected coastal/shoal and shelf/trough habitat (chi², p < 0.025-0.001), in all ice conditions. In the Alaskan Beaufort Sea, bowheads selected shelf waters and white whales chose slope waters, without regard to transport conditions (chi², p < 0.01-0.001). In the northern Chukchi Sea, gray whales selected coastal/shoal habitat in high transport conditions (chi², p < 0.005), and shelf/trough habitat (chi², p < 0.001) during moderate and low transport conditions. Variability in distribution and habitat selection among these species is likely linked to prey availability at dissimilar trophic levels, although this hypothesis has yet to be rigorously tested. Des données d'observation réalisées en automne sur dix années (1982-1991) grâce à des relevés aériens au large de l'Alaska septentrional ont été analysées dans le cadre de recherches sur la variabilité dans la distribution des cétacés et la sélection de leur habitat. On a calculé les indices de sélection de l'habitat pour la baleine boréale, la baleine blanche et la baleine grise de Californie dans des conditions de glace épaisse, modérée et mince; et pour des conditions de transport (courants de déversement) important, moyen et faible dans le détroit de Béring. La baleine boréale choisissait des eaux peu profondes de l'intérieur du plateau continental durant les conditions de glace modérée et mince, et un habitat plus profond sur la pente durant ...